(Še vedno) dramatično stanje sodobne slovenske dramatike - Komljanec, Kim (Amfiteater (Ljubljana), 2019)
The wide diversity of Slovenian new writing for the stage stretches across a variety of genres, styles and content despite the director-centric model of theatrical production within which it is being written. Due to the continuously deficient and in parts completely lacking infrastructure, and the fact that the programming of government funded theatres consists predominantly of translated dramatic works, playwrights often find themselves excluded from the production process. Playwrights of different generations have already started to migrate abroad as their capabilities remain unexplored at home. Yet, with additional, more broadly conceived opportunities for collaboration, technical education, professional connections, academic reflection, and regular publication and translation, contemporary Slovenian playwriting could deliver added value in quality to theatre producers, practitioners and audiences.
Keywords: dramatiki; dramsko pisanje; playwrights; Semenič, Simona; Slovenian drama; slovenska dramatika